2018
DOI: 10.5123/s1679-49742018000400014
|View full text |Cite
|
Sign up to set email alerts
|

Evolução das desigualdades socioeconômicas na realização de consultas de pré-natal entre parturientes brasileiras: análise do período 2000-2015*

Abstract: Objective: to analyze evolution as to conducting seven or more prenatal consultations with pregnant women in Brazil, in the period 2000-2015 according to maternal education level and race/skin color of the newborn baby. Methods: this was a time series study based on Live Births Information System (SINASC) data; relative and absolute inequalities were investigated, adjusted for maternal age and gestational week in which childbirth occurred. Results: we analyzed approximately 48 million births; the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 22 publications
(28 reference statements)
1
28
0
13
Order By: Relevance
“…The women who choose to have abortions following a rape are similar in terms of educational levels, religion or race/color, but there was a high percentage of adolescents 14,17,18,19,20,21 . Studies from the 1990s showed a higher percentage of lower educational level among these women, compared to data from more recent years, which may reflect the change in educational profile of Brazilian women 36 .…”
Section: Discussionmentioning
confidence: 72%
“…The women who choose to have abortions following a rape are similar in terms of educational levels, religion or race/color, but there was a high percentage of adolescents 14,17,18,19,20,21 . Studies from the 1990s showed a higher percentage of lower educational level among these women, compared to data from more recent years, which may reflect the change in educational profile of Brazilian women 36 .…”
Section: Discussionmentioning
confidence: 72%
“…Although the results suggest that the ESF and mixed units have greater opportunity to perform care for pregnant women of black or brown color, 19 it is pointed out that these groups of pregnant women are unable to perform the recommended routine examinations, they have more commute during childbirth, have a reduced number of prenatal consultations 20 and overall have higher rates of inadequacy for prenatal care 21,22 . This situation reinforces the discussions presented that expanding access to prenatal care was not sufficient for inducing quality care 23 , and although EFS and mixed units are able to strengthen the continuity of care between services, they may not be able to effect care for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation was observed between the detection rate of syphilis and FHT coverage (0.6672; P < 0.05). Regarding sociodemographic and clinical characteristics, a higher proportion of infection was observed in women in the 20-to-29 age group (15,709 [51.8%]), those of brown ethnicity (19,641 [64.7%]), and those with low educational level (14,872 [49.2%] with primary school as the highest level of educational attainment), and 12,351 (40.7%) syphilis cases were diagnosed during the third trimester of gestation. Among these cases, 11,289 (37.2%) were primary syphilis ( Table 1).…”
mentioning
confidence: 93%
“…The decreasing trend in the proportion of pregnant women with low educational level, accompanied by an increase in the proportion of pregnant women with a higher educational level, may reflect access to health services. An analysis of almost 48 million births registered in Brazil between 2000 and 2015 has revealed that the number of prenatal consultations performed was higher in pregnant women with a higher level of education 15 . Knowledge about the rights and importance of prenatal consultations as well as better living conditions experienced by this part of the population may justify this finding 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation